The Chimeric Gracilis and Profunda Artery Perforator Flap: Characterizing This Novel Flap Configuration with Angiography and a Cadaveric Model - Hammond, Jacob B.; Teven, Chad M.; Flug, Jonathan A.; Jokerst, Clint E.; Howarth, Ashley L.; Shrout, Max A.; Laitinen, Marko A.; Foley, Brittany M.; Kruger, Erwin A.; Casey, William J., III; Rebecca, Alanna M. (Journal of Reconstructive Microsurgery, 2021)
Background A chimerically configured gracilis and profunda artery perforator (PAP) flap is highly prevalent based on recent computed tomography (CT)-imaging data. The purpose of this study is to further characterize the vascular anatomy of this novel flap configuration and determine the feasibility of flap dissection.Methods To characterize flap arterial anatomy, lower extremity CT angiograms performed from 2011 to 2018 were retrospectively reviewed. To characterize venous anatomy and determine the feasibility of flap harvest, the lower extremities of cadavers were evaluated.Results A total of 974 lower extremity CT angiograms and 32 cadavers were included for the assessment. Of the 974 CT angiograms, majority (966, 99%) were bilateral studies, yielding a total of 1,940 lower extremities (right-lower-extremity = 970 and left-lower-extremity = 970) for radiographic evaluation. On CT angiography, a chimerically configured gracilis and PAP flap was found in 51% of patients (n = 494/974). By laterality, chimeric anatomy was present in 26% of right lower extremities (n = 254/970) and 25% of left lower extremities (n = 240/970); bilateral chimeric anatomy was found in 12% (n = 112/966) of patients. Average length of the common arterial pedicle feeding both gracilis and PAP flap perforasomes was 31.1 ± 16.5 mm (range = 2.0–95.0 mm) with an average diameter of 2.8 ± 0.7 mm (range = 1.3–8.8 mm).A total of 15 cadavers exhibited chimeric anatomy with intact, conjoined arteries and veins allowing for anatomical tracing from the profunda femoris to the distal branches within the tissues of the medial thigh. Dissection and isolation of the common pedicle and distal vessels was feasible with minimal disruption of adjacent tissues. Chimeric flap venous anatomy was favorable, with vena commitante adjacent to the common pedicle in all specimens.Conclusion Dissection of a chimeric medial thigh flap consisting of both gracilis and PAP flap tissues is feasible in a cadaveric model. The vascular anatomy of this potential flap appears suitable for future utilization in a clinical setting.
Keywords: chimeric flap; medial thigh; cadaver dissection